PARADIGMA TEORI HUKUM FEMINIS TERHADAP PERATURAN PERLINDUNGAN HUKUM BAGI PEREMPUAN KORBAN KEKERASAN SEKSUAL DI INDONESIA - Fenita Dhea Ningrumsari; Nur Azisa; Wiwie Heryani (JURNAL ILMIAH LIVING LAW, 2022)
The research is aim to analyze the regulation of legal protection for women as victims of sexual violence through feminist legal theory viewpoint. This theory is reputed that law is made from male point of view, so that the existing rules are considered as a product of patriarchy. This research used normative legal research method, namely by library studies. The results show that the scope of preventive regulations of legal protection are still limited. Moreover, from feminist legal theory viewpoint, the existing legal protection regulations are gender-biased and not representing the voice of women as victims of sexual violence. Despite Indonesia already has laws and regulations to protect women from sexual violence, which is more victim perspective, yet is limited to only several applied.  A product of legal protection that accommodates the principles of feminist legal theory which are not limited to certain domestics is required.